Involvement of Nestin in the Progression of Canine Mammary Carcinoma. Issue 5 (September 2021) - Yoshimura, Hisashi; Moriya, Maiko; Yoshida, Ayaka; Yamamoto, Masami; Machida, Yukino; Ochiai, Kazuhiko; Michishita, Masaki; Nakagawa, Takayuki; Matsuda, Yoko; Takahashi, Kimimasa; Kamiya, Shinji; Ishiwata, Toshiyuki
Nestin, a class VI intermediate filament protein, is known to be expressed in various types of human neoplasms, including breast cancer, and is associated with their progression. However, its expression and role in canine mammary tumors remain unknown. We analyzed nestin expression in canine mammary tumors using in situ hybridization and immunohistochemistry. We also investigated its role in a canine mammary carcinoma cell line using RNA interference. Nestin expression was not observed in luminal epithelial cells of any of the 62 cases of benign mammary lesions examined, although myoepithelial cells showed its expression in most cases. In 16/50 (32%) primary mammary carcinomas and 6/15 (40%) metastases of mammary carcinomas, cytoplasmic nestin expression was detected in luminal epithelial cells. In luminal cells of primary mammary carcinomas, its expression was positively related to several pathological parameters that indicate high-grade malignancy, including histological grading ( P < .01), vascular/lymphatic invasion ( P < .01), Ki-67 index ( P < .01), and metastasis ( P < .05). Immunohistochemistry revealed that nestin expression was related to vimentin expression in mammary carcinomas ( P < .01). This relationship was confirmed using reverse transcription-quantitative polymerase chain reaction using 9 cell lines derived from canine mammary carcinoma ( P < .01). Finally, nestin knockdown in canine mammary carcinoma cells using small interfering RNA inhibited cell proliferation and migration based on WST-8, Boyden chamber, and cell-tracking assays. These findings suggest that nestin may at least partially mediate these behaviors of canine mammary carcinoma cells.